2012
DOI: 10.5005/jp-journals-10024-1152
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy of Tramadol and Butorphanol in Mandibular Third Molar Surgery: A Comparative Study

Abstract: Background Butorphanol tartrate, a mixed synthetic agonistantagonist opioid analgesic has been used for management of postoperative pain in minor and major surgical procedures.14,20 Tramadol hydrochloride is a centrally acting opioid which is effectively used in postoperative pain in various minor and major surgeries. Materials and methods Twenty subjects selected randomly received butorphanol tartrate 1 mg intramuscular and 20 subjects received tramadol hydrochloride 50 mg intramuscular after the removal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…At 1 week, 1 month, and 3 months in the current trial, the pain score decreased in a highly statistically significant manner. This was in line with the findings of studies by Al-Kibsi et al [5] and Hassan et al [11], which found that administering butorphanol at a dose of 1 mg was more effective than tramadol at a dose of 50 mg for postoperative analgesia following the removal of third molar impaction. It was also consistent with the findings of the study by Bhumika et al [12], which came to the conclusion that efficiency and pain relief were reduced in patients with arthritis by roughly 80% in a dose-dependent, stereo-selective, antagonistreversible way [8].…”
Section: Discussionsupporting
confidence: 92%
“…At 1 week, 1 month, and 3 months in the current trial, the pain score decreased in a highly statistically significant manner. This was in line with the findings of studies by Al-Kibsi et al [5] and Hassan et al [11], which found that administering butorphanol at a dose of 1 mg was more effective than tramadol at a dose of 50 mg for postoperative analgesia following the removal of third molar impaction. It was also consistent with the findings of the study by Bhumika et al [12], which came to the conclusion that efficiency and pain relief were reduced in patients with arthritis by roughly 80% in a dose-dependent, stereo-selective, antagonistreversible way [8].…”
Section: Discussionsupporting
confidence: 92%
“…showed that butorphanol 1 mg was more effective than T 50 mg in respect to post-operative analgesia in mandibular third molar surgery. [23] Another study by deCosta Arajua et al . has noted that nimesulide and T chlorhydrate demonstrate similar preemptive analgesic effects when used in lower third molar surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…In painless gastrointestinal endoscopy, the use of butorphanol tartrate not only reduces the incidence of physical movement and coughing in patients, which is conducive to the smooth operation of endoscopy, but also reduces the amount of propofol used, reduces the pain of propofol injections, and reduces the incidence of adverse reactions, such as dizziness, drowsiness, and respiratory depression, and shortens the recovery time of patients [18,19] . The analgesic effect of using Butorphanol for mandibular third molar extraction is significantly better than Tramadol in the dental clinic [20] . The use of Butorphanol tartrate in painless abortion, with its longer sedative-analgesic effect, can effectively relieve the pain of postoperative uterine contractions, lower incidence of nausea and vomiting and respiratory depression, also improves the intraoperative and postoperative safety and comfort of patients [21] .…”
Section: Butorphanol Tartratementioning
confidence: 95%